lo g 2 a = 1 ∏ 2 0 1 9 b = 1 ∏ 2 0 1 9 ( 1 + e 2 0 1 9 2 π i a b )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is worth noting that we are calculating the Dirichlet convolution i ⋆ φ of the function i ( n ) = n and φ . Since both i and φ are multiplicative, so is i ⋆ φ . Since ( i ⋆ φ ) ( p ) = p × 1 + 1 × ( p − 1 ) = 2 p − 1 for any prime p , we get the answer for 2 0 1 9 = 3 × 6 7 3 . The fact that i ⋆ φ is multiplicative would make the calculation of the result for a different year much easier.
Thank you for the comment.
Problem Loading...
Note Loading...
Set Loading...
We first claim that if n is odd, then ∏ b = 1 n ( 1 + e 2 π i a b / n ) = 2 g cd ( a , n ) . To see this, write d = g cd ( a , n ) and a = d a 1 , n = d n 1 with g cd ( a 1 , n 1 ) = 1 .
Then a 1 , 2 a 1 , … , n 1 a 1 modulo n 1 is a permutation of 1 , 2 , … , n 1 modulo n 1 , and so ω a 1 , ω 2 a 1 , … , ω n 1 a 1 is a permutation of ω , ω 2 , … , ω n 1 ;
it follows that for ω = e 2 π i / n 1 , we have:
b = 1 ∏ n 1 ( 1 + e 2 π i a b / n ) = b = 1 ∏ n 1 ( 1 + e 2 π i a 1 b / n 1 ) = b = 1 ∏ n 1 ( 1 + ω b ) .
Now since the roots of z n 1 − 1 are ω , ω 2 , … , ω n 1 ,
it follows that: z n 1 − 1 = ∏ b = 1 n 1 ( z − ω b ) . Setting z = − 1 and using the fact that n 1 is odd gives ∏ b = 1 n 1 ( 1 + ω b ) = 2 .
Finally, ∏ b = 1 n ( 1 + e 2 π i a b / n ) = ( ∏ b = 1 n 1 ( 1 + e 2 π i a b / n ) ) d = 2 d , and we have proven the claim.
From the claim we find that:
lo g 2 ( a = 1 ∏ 2 0 1 9 b = 1 ∏ 2 0 1 9 ( 1 + e 2 π i a b / 2 0 1 9 ) ) = a = 1 ∑ 2 0 1 9 lo g 2 ( b = 1 ∏ 2 0 1 9 ( 1 + e 2 π i a b / 2 0 1 9 ) ) = a = 1 ∑ 2 0 1 9 g cd ( a , 2 0 1 9 ) .
Now for each divisor d of 2 0 1 9 , there are ϕ ( 2 0 1 9 / d ) integers between 1 and 2 0 1 9 inclusive whose g cd with 2 0 1 9 is d . Thus a = 1 ∑ 2 0 1 9 g cd ( a , 2 0 1 9 ) = d ∣ 2 0 1 9 ∑ d ⋅ ϕ ( 2 0 1 9 / d ) . We factor 2 0 1 9 = p q with p = 3 and q = 6 7 3 , and calculate:
\(\begin{align*} &\sum_{d|pq} d\cdot \phi(pq/d) \\ &= 1 \cdot (p-1)(q-1) + p \cdot (q-1) + q\cdot (p-1) + pq \cdot \\
&\quad = (2p-1)(2q-1)= (2\times 3-1)(2\times 673 -1)=6725. \end{align*}\)